2020
DOI: 10.1002/ehf2.13064
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma endothelin‐1 is related to low natriuresis, clinical signs of congestion, and poor outcome in acute heart failure

Abstract: Aims Endothelin-1 (ET-1) is a potent vasoconstrictor, which regulates renal and vascular function. We aimed to relate plasma levels of ET-1 with the clinical picture and outcomes in acute heart failure (AHF). Methods and results We studied 113 patients with AHF [mean age 65 ± 13 (years), median (upper and lower quartiles) N-terminal pro-B-type natriuretic peptide, 5422 (2689; 8582) (pg/mL)], in whom plasma levels of ET-1 were serially measured at admission (10.8 ± 5.2), Day 1 (9.5 ± 3.4), and Day 2 (8.9 ± 3.8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…In our study patients did not uniformly suffer from inability to excrete sodium, as those from RAAS − /− and RAAS +/+ profiles excreted urine with significantly higher sodium concentration during first 48 h of hospitalization, which has also translated into an average shorter hospital stay. This is in agreement with our previous report linking natriuresis with other vasoactive molecule (endothelin-1) in AHF [24].…”
Section: Discussionsupporting
confidence: 94%
“…In our study patients did not uniformly suffer from inability to excrete sodium, as those from RAAS − /− and RAAS +/+ profiles excreted urine with significantly higher sodium concentration during first 48 h of hospitalization, which has also translated into an average shorter hospital stay. This is in agreement with our previous report linking natriuresis with other vasoactive molecule (endothelin-1) in AHF [24].…”
Section: Discussionsupporting
confidence: 94%
“…These findings revealed that the strong endothelin system activation reflected not only cardiac function but also renal and liver functions and personal nutritional status. The important biological functions of this comprehensive indicator in multiple organs were consistent with previous works ( 13 , 24 , 26 , 27 ).…”
Section: Discussionsupporting
confidence: 91%
“…Baseline concentration of ET-1 was proportional to the severity of disease (in terms of NYHA class and LVEF) and it was revealed to be an independent outcome predictor of all-cause morbidity and mortality [44]. More recently, ET-1 role was also investigated in acute HF patients, and it was demonstrated that its concentration correlates with clinical signs of congestion (fluid overload), low natriuresis (i.e., urine sodium excretion), and, finally, that levels of ET-1 are also a significant prognostic factor of one-year mortality due to acute HF [46].…”
Section: Et-1 and Mpomentioning
confidence: 99%